2022
DOI: 10.1002/aid2.13315
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Mac‐2 binding protein glycosylation isomer (M2BPGi) with AST to platelet ratio index (APRI), fibrosis 4 Score (FIB‐4), and nonalcoholic fatty liver disease (NAFLD) fibrosis score (NFS) for NAFLD patients

Abstract: The serum level of Mac-2 binding protein glycosylation isomer (M2BPGi) has been found to increase with the severity of liver fibrosis in biopsy-proved nonalcoholic fatty liver disease (NAFLD). However, the comparison of M2BPGi with noninvasive fibrosis markers such as AST to platelet ratio index (APRI), Fibrosis 4 Score (FIB-4), and NAFLD fibrosis score (NFS) in NAFLD patients remains unclear. The participants of Tzu Chi NAFLD cohort (TCNC) including health controls or NAFLD patients were enrolled in Taipei Tz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…5,9,10,12,14 Cheng et al found that aging increases M2BPGi levels in healthy patients. 17 This finding may explain why our cut-off results were more than one. However, the effects aging on M2BPGi levels require further research.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…5,9,10,12,14 Cheng et al found that aging increases M2BPGi levels in healthy patients. 17 This finding may explain why our cut-off results were more than one. However, the effects aging on M2BPGi levels require further research.…”
Section: Discussionmentioning
confidence: 89%
“…It has been demonstrated that M2BPGi is a good biomarker for evaluating liver fibrosis. [4][5][6][7][8][9][10][11][12][13][14][15][16][17] A stepwise diagnostic analysis has not yet been conducted to determine the value of M2BPGi in assessing liver fibrosis. Here, we aimed to investigate the use of M2BPGi as a single or combined diagnostic modality for liver fibrosis in CHB patients through a stepwise diagnostic analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 4 , 5 M2BPGi has been widely used to predict liver fibrosis and cirrhosis in different chronic liver diseases. 5 18 In several previous studies, M2BPGi helped to diagnose liver fibrosis in a CHB population 6 , 11 and it could be used as a single predictor variable to diagnose liver fibrosis grade. 12 , 13 This marker could also complement and be used with other modalities.…”
Section: Introductionmentioning
confidence: 99%
“…Cheng et al presented the study results of the correlation of Mac-2 binding protein glycosylation isomer (M2BPGi) serum level with the other documented noninvasive biomarkers or panels in a single-center retrospective NAFLD database. 5 M2BPGi has been vigorously studied as a marker for fibrosis in chronic hepatitis B virus infection, chronic hepatitis C virus infection, nonalcoholic steatohepatitis, and even hepatocellular carcinoma. [6][7][8][9] The cross-sectional study measured the serum levels of the recently-identified glycosylation isoform of Mac-2 binding protein in both NAFLD and healthy controls.…”
mentioning
confidence: 99%